(untitled) (Italian Journal of Public Health, 2009)
Background: Tribes constitute a considerable proportion (8.2%) of the Indian population. Most of them are underprivileged. In general, data are scarce on the nutritional status of the various tribal and rural populations of India. The principal aim of this study was to understand the age-trend and ethnic variations in anthropometric characteristics and nutritional status in three adult male populations (Oraon, Sarak and Dhimal) of eastern India. This report is significant because of the new and empirical data on these communities. Oraon is an age-old tribe while Dhimal is a much less known small community and Sarak is also a less studied group. Methods: A cross-sectional study in the perspective of anthropometric assessment of health and nutritional status has been undertaken among the adult male samples (aged 18 years and above) of three endogamous and tribal communities of eastern India, viz., Oraons (n=290), Saraks (n=158) and Dhimals (n=159). The major objective of the present study was to report nutritional status, based on Body Mass Index (BMI), Mid Upper Arm Circumference (MUAC), Waist-Hip Ratio (WHR) and Rohrer Index (RI) of the adult males of the Oraon and Sarak communities of the district of Ranchi in Jharkhand and among the Dhimals of Darjeeling district in West Bengal. Results: Results describing the situation of the Oraons was worse (53.10%) followed by the Saraks (27.85%) and the Dhimals (27.04%) with respect to low Body Mass Index (BMI) and high degree of undernutrition (BMI < 18.49 kg/mt2). Health profile of the adult males evaluated by Rohrer Index (RI) documented that 66.89% of the Oraons had subnormal health the condition (RI ≤ 1.19). In addition, 51.57% of Dhimals and 39.87% of the Saraks also exhibited to have subnormal state of health in this appraisal. Sizeable proportion of each of these populations was observed to have poor nutrition, as evaluated by the standard cut-off values of MUAC. Conclusions: Results displayed prevalence of high level of undernutrition and considerable percentages of non-obesity in these populations. Age variation of anthropometric characteristics and nutritional status grossly showed conspicuous negative trend of the parameters with the advancement of age with a few minor exceptions